Recommendations for ethical and responsible use of artificial intelligence in digital agriculture - Dara, Rozita; Hazrati Fard, Seyed Mehdi; Kaur, Jasmin (Frontiers in Artificial Intelligence, 2022)
Artificial intelligence (AI) applications are an integral and emerging component of digital agriculture. AI can help with sustainable production in agriculture by enhancing operations and decision-making to manage and improve farm management. Recommendations about the soil condition and pesticides or automatic devices for milking and apple picking are examples of AI applications in digital agriculture. Although AI offers many benefits in farming, AI systems may raise ethical issues and risks that should be assessed and proactively managed. Poor design and configuration of intelligent systems may impose harm and unintended consequences to digital agriculture. Invasion of farmers’ privacy, damaging animal welfare due to robotic technologies, and lack of accountability for issues resulting from the use of AI tools are examples of ethical challenges in digital agriculture. This paper examines the ethical challenges that can harm the agricultural system by integrating six ethical principles, including fairness, transparency, accountability, sustainability, privacy, and robustness. This study provides recommendations for agriculture technology providers (ATPs) and policymakers on how to proactively mitigate ethical issues that may arise from the use of AI in farming. These recommendations cover a wide range of ethical considerations, such as addressing farmers’ privacy concerns, ensuring reliable AI performance, enhancing sustainability of AI system use, and reducing AI bias.